2014
DOI: 10.4049/jimmunol.1302174
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression in the Gitr Locus Is Regulated by NF-κB and Foxp3 through an Enhancer

Abstract: Gitr and Ox40, two members of the TNFR superfamily, play important roles in regulating activities of effector (Teff) and regulatory (Treg) T cells. Their gene expression is induced by T cell activation, and further upregulated in Foxp3+ Treg. Although the role of Foxp3 as a transcriptional repressor in Treg is well established, the mechanisms underlying Foxp3-mediated transcriptional upregulation remain poorly understood. This transcription factor seems to upregulate expression not only of Gitr and Ox40, but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…GITR does not express in Jurkat T cells . FOXP3 was previously reported to activate GITR transcription in Treg cells . However, the overexpression of FOXP3 in Jurkat T cells did not induce GITR expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GITR does not express in Jurkat T cells . FOXP3 was previously reported to activate GITR transcription in Treg cells . However, the overexpression of FOXP3 in Jurkat T cells did not induce GITR expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given that FoxP3 is the lineage specific transcription factor that differentiates Treg and Tconv cells, it is possible that FoxP3 itself coordinates Treg-specific p65-binding and activity. It was previously suggested that FoxP3 and p65 may influence NF-κB activity, for instance on the GITR locus (Tone et al, 2014). Analysis of our ChIPseq and public data showed binding for both p65 and Foxp3 on multiple Treg genes, including Foxp3 itself, Ikzf2, Lrrc32 or Ctla4 .…”
Section: Discussionmentioning
confidence: 99%
“…Cambogin did not alter the expression of TLR4 and Myd88, but cambogin suppressed the MAPK and IKK/IκB pathways, which play leading roles in the inflammatory process. Indeed, it is complicated and difficult to determine the specific mechanism of cambogin on Foxp3 expression, as the role of transcription factors, such as AP-1, NF-κB, NF-AT and stat5, in Foxp3 expression during Treg cell development and functional regulation is still debatable (Bettelli et al, 2005;Lee et al, 2008;Tone et al, 2014;Harusato et al, 2017). Nevertheless, the results of the present study demonstrated that cambogin promotes the expression of Foxp3 expression in an inflammatory environment.…”
Section: Figurementioning
confidence: 99%